(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores the effects of Entrepreneurial Orientation (EO) on venture capitalist investment in Technology Medium Scale Enterprises (Tech MSEs) in North-Central, Nigeria, while considering the moderating role of organizational culture. The research highlights the critical importance of Tech MSEs as engines of economic growth and innovation, particularly in emerging markets. Utilizing a quantitative survey design, data were collected from 358 tech MSEs owners across various sectors for analysis. The findings indicate a significant positive relationship between EO and venture capital investment, underscoring that firms with a strong entrepreneurial orientation are more likely to attract funding. Organizational culture was found to moderate this relationship, enhancing the effectiveness of EO in securing investments. The results suggest that fostering a supportive organizational culture can mitigate perceived risks for investors, thereby improving the attractiveness of Tech MSEs. This study contributes valuable insights for entrepreneurs and policymakers, emphasizing the need for strategic alignment between entrepreneurial practices and organizational culture to enhance venture capital attraction and promote sustainable growth in the Tech sector.